2013
DOI: 10.1128/mcb.01748-12
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Inhibits Autophagic Flux, Activating the Nrf2-Keap1 Pathway in a p62-Dependent Manner

Abstract: The Nrf2-Keap1 signaling pathway is a protective mechanism promoting cell survival. Activation of the Nrf2 pathway by natural compounds has been proven to be an effective strategy for chemoprevention. Interestingly, a cancer-promoting function of Nrf2 has recently been observed in many types of tumors due to deregulation of the Nrf2-Keap1 axis, which leads to constitutive activation of Nrf2. Here, we report a novel mechanism of Nrf2 activation by arsenic that is distinct from that of chemopreventive compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
172
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(182 citation statements)
references
References 59 publications
8
172
1
1
Order By: Relevance
“…The p62/sequestosome 1 protein is a multifunction, ubiquitin-binding adapter protein that serves multiple cellular functions for autophagy, apoptosis, reactive oxygen species (ROS) signaling, and cancer development (2,3). The accumulated p62 competitively binds to the Nrf2-binding site of Keap1 and promotes the constitutive activation of Nrf2 transcriptional programs (4). Thus, p62 accumulation activates Nrf2 and Nrf2 target gene expression (5,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The p62/sequestosome 1 protein is a multifunction, ubiquitin-binding adapter protein that serves multiple cellular functions for autophagy, apoptosis, reactive oxygen species (ROS) signaling, and cancer development (2,3). The accumulated p62 competitively binds to the Nrf2-binding site of Keap1 and promotes the constitutive activation of Nrf2 transcriptional programs (4). Thus, p62 accumulation activates Nrf2 and Nrf2 target gene expression (5,6).…”
mentioning
confidence: 99%
“…It has been shown that inducible Nrf2 activation is important in the anticancer effects of many natural compounds, including phenethyl isothiocyanate, curcumin, and resveratrol (12 859-323-1059; E-mail: xshi5@email.uky.edu. 4 The abbreviations used are: Nrf2, nuclear factor erythroid 2-related factor; ROS, reactive oxygen species; ARE, antioxidant response element; NF-B, nuclear factor B; Keap1, kelch-like ECH-associated protein 1; LC3, microtubule-associated protein 1 light chain 3; ABT-263, 4-(4- -induced carcinogenesis (cell transformation) by an up-regulation of antioxidants to reduce As 3ϩ -induced ROS; however, once a cell is transformed, Nrf2 is oncogenic by inducing apoptosis resistance. This study also will examine how constitutive activation of Nrf2 contributes to apoptosis resistance as well as a decrease in ROS generation and tumorigenesis in transformed cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of possible explanation can be found in the article of T. Schwerdtle et al [46] about S(ulphur)-containing arsenic metabolites that modulated total cellular glutathione amount at picomolar concentrations. Recently it was shown that sodium arsenite treatment of normal cells induces prolonged activation of Nrf2 through autophagy dysfunction [29]. This observation corresponds to the fact found in certain human cancer types, where high sustained level of Nrf2 provides the resistance to treatment.…”
Section: Realgar Nanoparticlesmentioning
confidence: 81%
“…Metabolism of inorganic arsenic contributes to alteration of large number of transcription factors [28][29][30][31]. Among them Nrf2 plays a crucial role in the cellular protection against oxidative stress regulating the cellular antioxidant response.…”
Section: Realgar Nanoparticlesmentioning
confidence: 99%